Measuring Micro-Friction Torque in MEMS Gas Bearings - Xudong Fang; Huan Liu (Sensors, 2016)
An in situ measurement of micro-friction torque in MEMS gas bearings, which has been a challenging research topic for years, is realized by a system designed in this paper. In the system, a high accuracy micro-force sensor and an electronically-driven table are designed, fabricated and utilized. With appropriate installation of the sensor and bearings on the table, the engine rotor can be driven to rotate with the sensor using a silicon lever beam. One end of the beam is fixed to the shaft of the gas bearing, while the other end is free and in contact with the sensor probe tip. When the sensor begins to rotate with the table, the beam is pushed by the sensor probe to rotate in the same direction. For the beam, the friction torque from the gas bearing is balanced by the torque induced by pushing force from the sensor probe. Thus, the friction torque can be calculated as a product of the pushing force measured by the sensor and the lever arm, which is defined as the distance from the sensor probe tip to the centerline of the bearing. Experimental results demonstrate the feasibility of this system, with a sensitivity of 1.285 mV/μN·m in a range of 0 to 11.76 μN·m when the lever arm is 20 mm long. The measuring range can be modified by varying the length of the lever arm. Thus, this system has wide potential applications in measuring the micro-friction torque of gas bearings in rotating MEMS machines.